(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Relevance. Excimer laser vision correction using LASIK and Femto-LASIK is one of the most common surgical procedures for ametropia. However, despite their effectiveness, corneal regeneration processes after surgery may vary significantly depending on the method of flap formation. Cytokine balance plays a key role in modulating the inflammatory response and reparative processes, which determine the clinical outcomes of surgical intervention. Objective. To assess the levels of cytokines (IL-1β, TNF-α, IL-4) in the tear fluid of patients after LASIK and Femto-LASIK to analyze the inflammatory response and corneal regeneration. Materials and methods. The study included 40 patients (80 eyes) with myopia and astigmatism. Cytokine levels were measure using the ELISA method on the third day after surgery. Results. In the LASIK group, higher levels of IL-1β and TNF-α were detected, correlating with a pronounced inflammatory response and delayed healing (p<0.05). In the Femto-LASIK group, IL-4 levels were higher, contributing to faster corneal recovery. Conclusions. Femto-LASIK is associated with a lower inflammatory response and accelerated epithelialization compared to LASIK, confirming its advantages in the postoperative period.